Petrographic and geochemical characteristics of Eocene (?) basic igneous rocks outcropping around Gülümuşağı (Malatya) - Sar, Abdullah (Gumushane University, 2024)
Eocene (?) aged magmatic rocks cropping out around Gülümuşağı in Malatya province in the Southeastern Anatolian Orogenic Belt (SAOB) are in the composition of gabbro and diorite and petrographically consist of plagioclase, pyroxene and amphibole minerals. The gabbros and diorites under investigation have low-medium K character, negative trends in Rb, P, Nb and Ti elements, and positive trends in Sr and Ba values in the trace element diagram normalized according to the Primary Mantle. It shows an almost horizontal trend in the trace element variation diagram normalized according to chondrite. The LaN/LuN ratios between light rare earth elements (LREE) and heavy rare earth elements (HREE) in the gabbros and diorites under investigation vary between 1.31 and 1.53 (AS17=0.53, AS20=5.35) and show weak-medium levels of fractionation. Gabbro and diorite-type rocks show positive Eu anomalies, and EuN/Eu* values vary between (1.01-1.46). Gabbro and diorites have relatively low La/Yb (0.63-6.31) and Nb/La (0.42-0.75) ratios, indicating lithospheric mantle/lithospheric-asthenospheric mantle origin. Low Zr/Hf (12.6-39.3) and Nb/Yb (0.31-3.26) ratios suggest that these rocks are formed from a depleted mantle source. The role of fractional crystallization is greater than assimilation in developing the main magma that forms the gabbros and diorites under investigation. In light of all the data, it is thought that the main magma of Eocene (?) aged gabbros and diorites was derived from a source containing spinel representing shallow depths. © 2024, Gumushane University. All rights reserved.
Gülümuşağı (Malatya) çevresinde yüzeyleyen Eosen (?) yaşlı bazik magmatik kayaçların petrografik ve jeokimyasal özellikleri
Keywords: Gabbro/diorite; Geochemistry; Gülümuşağı; Petrogenesis; Petrography